STRATEGI BRANDING PRODUK DALAM MENGEMBANGKAN USAHA DI DESA SINDANGSARI - Lestari, Devi Ayu; Khadijah, Siti; Marginingsih, Ria (An-Nizam, 2023)
MSMEs have an important role in contributing to the Indonesian economy in building branding, MSMEs need knowledge about the importance of brands as invisible assets where branding becomes an inseparable part of how the strategy for marketing products is seen from the problems that occur in Sindangsari village, namely low competitiveness MSME products in villages, this is possible due to the inability of MSMEs to create identity in their products by using the implementation method which is carried out through outreach to MSME actors regarding product branding, product branding training, namely logo editing through Canva and evaluation regarding the steps that have been carried out to look at the understanding of MSME actors regarding product branding and increase motivation and be innovative regarding the role of product branding in increasing sales. The result of this activity is that people can understand how to introduce products or create an identity for siomay business products, understand how to create a brand and create logo designs, labels, banners and brochures for product identities.